2005
DOI: 10.1161/01.str.0000181740.74005.ee
|View full text |Cite
|
Sign up to set email alerts
|

The Association of C-Reactive Protein Levels With Carotid Intima-Media Complex Thickness and Plaque Formation in the General Population

Abstract: Background and Purpose-An inflammatory response has been associated with the development of atherosclerosis. Our aim was to clarify which atherosclerotic changes (intima-media complex thickness [IMT] increase, plaque formation, and arterial dilatation) are associated with C-reactive protein (CRP) levels and to determine whether there are any gender differences. Methods-Carotid ultrasound and measurement of high-sensitivity CRP (hs-CRP) levels were performed in 2056 subjects selected from a general population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 34 publications
(30 reference statements)
4
73
1
6
Order By: Relevance
“…Carotid plaque was defined as a regional intimal thickening of 41.4 mm in height or double the adjacent IMT height. 9 Inter-observer correlation between repeated IMT measurements from 13 subjects was 0.97 (Po0.001) for mmIMT and 0.91 (Po0.001) for maximum IMT.…”
Section: Carotid Ultrasoundmentioning
confidence: 84%
“…Carotid plaque was defined as a regional intimal thickening of 41.4 mm in height or double the adjacent IMT height. 9 Inter-observer correlation between repeated IMT measurements from 13 subjects was 0.97 (Po0.001) for mmIMT and 0.91 (Po0.001) for maximum IMT.…”
Section: Carotid Ultrasoundmentioning
confidence: 84%
“…Tamaki et al reported that baPWV was associated with the existence of plaque, but not with the severity of plaque in patients with cerebral thrombosis (24). In another study, plaque score was reported to be more closely related to serum CRP level than to IMT (25). CRP level has also been shown to be correlated with visceral fat accumulation and therefore linked to the metabolic syndrome and type 2 diabetes (26,27).…”
Section: Discussionmentioning
confidence: 94%
“…The UK Prospective Diabetes Study (UKPDS) confirmed that strict control of blood pressure could significantly reduce the incidence of peripheral vascular diseases in diabetic patients (UKPDS Group, 1998). Some studies (Makita et al, 2005) have proved that longterm smoking could cause vascular endothelial injury, increasing the levels of high-sensitivity CRP and thus leading to atherosclerosis. The most recent 17 prospective studies and 14 cross- sectional studies showed that the smoking dose was related to the incidence and development of peripheral arterial diseases, and that the prevalence of active smokers increased by 2.3 times (Willigendael et al, 2004).…”
Section: Discussionmentioning
confidence: 99%